THE EFFECT OF FORMAL SCHEMA ON COLLEGE ENGLISH LISTENING COMPREHENSION IN EFL - Liyan, Shi; Duqin, Wang; Chunyan, Chu (Universitas Pendidikan Indonesia, 2014)
Abstract: Listening comprehension used to be thought of as a passive skill, and listeners were called asâ€œtape-recorderâ€ (Anderson Lynch,1988). But in fact it is an active process, in which what the listener wants to get is an adequate understanding of what the speaker said and what the speaker meant. To achieve this purpose, English listeners should utilize contextual clues, background knowledge and depend on many learning strategies. Active listeners will understand what the speakers said with relevant background knowledge and their particular purpose. In recent years, there has been a lot of progress English listening teaching in China, and studies on application of schema theory into listening comprehension have become more and more popular in both pedagogical theory and experiments. Schema is one of major factors that affect peopleâ€™s listening comprehension. The present study, with second-year non-English majors as subjects, aimed to investigate the effect of formal schema on college English listening comprehension. It was found that when there is a lack of relevant formal schema, there will be a short-circuit of listening comprehension. It is also proved that activation of formal schema improves college studentsâ€™ listening comprehension. Therefore, it is necessary to improve college studentsâ€™ language skills and help them build up relevant formal schema as well.Â Key words: formal schema, listening comprehension, college EnglishÂ PENGARUH SKEMA FORMAL TERHADAP PEMAHAMAN MENYIMAK BAHASA INGGRIS PADA KELAS BAHASA INGGRIS SEBAGAI BAHASA ASINGÂ Abstrak: Pemahaman menyimak sebelumnya seringkali dianggap sebagai keterampilan pasif, dan para pendengarnya disebut â€œalat rekamâ€ (Anderson Lynch, 1988). Tapi, kenyataannya, menyimak adalah proses aktif, dimana apa yang diinginkan pendengar adalah pemahaman yang memadai terhadap apa yang dikatakan oleh penutur dan maksud dari penutur. Untuk mencapai tujuan ini, para penyimak bahasa Inggris harus memanfaatkan petunjuk-petunjuk kontekstual, pengetahuan latar belakang dan bergantung pada berbagai strategi belajar. Para penyimak aktif akan memahami apa yang dikatakan penutur dengan pengetahuan yang relevan dan tujuan khususnya. Akhir-akhir ini, ada banyak kemajuan dalam pengajaran menyimak di Cina, dan kajian-kajian mengenai penerapan teori skema pada pemahaman menyimak telah menjadi semakin populer baik dalam teori maupun eksperimen pedagogik. Skema adalah salah satu faktor utama yang mempengaruhi pemahaman menyimak orang-orang. Kajian ini, dengan mahasiswa non-bahasa Inggris tingkat dua sebagai subyeknya, bertujuan menyelidiki pengaruh dari skema formal terhadap pemahaman menyimak bahasa Inggris di perguruan tinggi. Ditemukan bahwa ketika ada kekurangan akan skema formal yang relevan, akan ada â€œhubungan arus pendekâ€ dalam pemahaman menyimak. Terbukti juga bahwa aktivasi skema formal meningkatkan pemahaman menyimak para mahasiswa. Karena itu, penting untuk meningkatkan keterampilan-keterampilan bahasa mahasiswa dan juga membantu mereka membangun skema formal yang relevan.Â Kata kunci: Skema formal, pemahaman menyimak, bahasa Inggris perguruan tinggi